(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): How management quality influences excellence in public healthcare, stress management and health preservation of Slovenian physicians? Purpose: The purpose of this research is to determine the attitude towards health of Slovenian physicians who work in public healthcare on both primary and tertiary level, their way of coping with stress, health preservation, and to develop a model of management quality and excellence in public healthcare. Such a model should be based on the improvement of quality management in healthcare, and especially on Slovenian physicians’ work excellence. Method: The key statistical method applied in the research was Structural Equation Models (SEM). The advantage of this approach is that all the influences and relations can be included in the model. The analysis was performed with the statistical tool AMOS – the programme application of IBM SPSS 22.0. We used method of testing the differnces in mean values for different groups (t-test or non-parametric Mann-Whitney test). Results: Based on the research results, we have established that we have obtained enough data to support changes in Public health. Leaders must be able to leap realize into organizational excellence of the physicians in Slovenian public. Organisation.The research was conducted at the University Medical Centre in Ljubljana and Maribor, via a web survey published in the Bulletin of Medical Chamber of Slovenia. Society: According to the research results, we concluded that radical changes are needed in public healthcare, which can contribute to the management quality and physicians’ excellence improvement. This way the society gets healthy and stress-free physicians who will perform their tasks with enthusiasm, as they will operationally achieve high effectiveness and efficiency. Originality: The contribution to science lies in the fact that this is a original scientific contribution since the study on the subject in question has not yet been carried out in Slovenia. Limitations/Future Research: This research was limited only on the physicians at the primary and tertiary level. The physicians at the secondary level remained out of scope, and they can be included in future research.